ПЕРВЫЙ АРХЕТЕКСТ О ВОЗВЫШЕННОМ: ПСЕВДО-ЛОНГИН (Filološke pripombe, 2019)
The objective of this article is to reconsider the main ideas of Pseudo Longinus’ book «On the Sublime», the work in which for the first time, twenty centuries ago, and the category of sublimity was analyzed. Today, at the beginning of the new millennium the sublime is in fashion. On the one hand, that is the reason why we are witnessing increased theoretical interest for the sublimity, and on the other hand this is the result of rereading the ideas of Pseudo Longinus, which are now being interpreted as successful connection between rhetoric, theory of literature and aesthetics. All this contributes to the fact that the work of Pseudo Longinus «On the Sublime» is considered as one of the three or four arche-texts (together with those of Edmund Burke, Immanuel Kant and Jean-François Lyotard) in regard with the notions of the sublime and the sublimity. This is a text without which even today one can not imagine the researches neither in the field of aesthetics, nor theory of literature, or rhetoric.